DPPH Radical Capture Test of Sumbawa Oil and Identification of Compound Content Using GC-MS - Wardani, Ray Haerul; Permatasari, Lina; Hidayati, Agriana Rosmalina; Hanifa, Nisa Isneni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Free radicals are reactive fragments that can trigger a variety of chronic diseases. Antioxidant compounds are needed to counteract the attack of free radicals. Sumbawa oil is one of the natural traditional remedies that has the potential to be a natural antioxidant because it contains compounds such as lauric acid, palmitic acid, linoleic acid, stearic acid, and methyl palmitate. The study aimed to determine the metabolite compounds contained in the Sumbawa oil brand “Rimba” and their activity to capture the DPPH free radical. The Sumbawa oil determined their metabolite compounds using Gass Chromatography-Mass Spectrometry (GC-MS). The antioxidant activity of Sumbawa oil was analyzed using the DPPH radical capture method. The GC spectra showed the 5 compounds detected in the Sumbawa oil. In addition, the MS spectra showed these 5 compounds were delta-3-carene, trans-caryophyllene, palmitic acid, palmitoleic acid, and stearic acid. The antioxidant activity of Sumbawa oil was found to be very weak with an IC50 value of 13.49 ± 0.34 mg/mL. Therefore, Palmitoleic acid and palmitic acid were reported to have potential antioxidant activity. These compounds were lipophilic antioxidants that did not properly detect their antioxidant activity using the DPPH method. So, the antioxidant activity of Sumbawa oil was recommended to be analyzed using the β-carotene bleaching method.